2015
DOI: 10.1103/physrevlett.114.108001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Structural Flow Defects in Disordered Solids Using Machine-Learning Methods

Abstract: We use machine learning methods on local structure to identify flow defects -or regions susceptible to rearrangement -in jammed and glassy systems. We apply this method successfully to two disparate systems: a two dimensional experimental realization of a granular pillar under compression, and a Lennard-Jones glass in both two and three dimensions above and below its glass transition temperature. We also identify characteristics of flow defects that differentiate them from the rest of the sample. Our results s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
373
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(389 citation statements)
references
References 41 publications
12
373
1
3
Order By: Relevance
“…There is a long tradition of associating glassy behavior with geometrical features associated with the arrangements of particles around a given particle, see e.g. [13][14][15][16][17], and our work on disks in a narrow channel is entirely consistent with these ideas. In our earlier work [6,7] a length scale ξ associated with zigzag order has been determined from the decay with s of the correlation function y i y i+s ∼ (−1) s exp(−s/ξ) .…”
Section: Fig 1: (Color Online)supporting
confidence: 74%
See 3 more Smart Citations
“…There is a long tradition of associating glassy behavior with geometrical features associated with the arrangements of particles around a given particle, see e.g. [13][14][15][16][17], and our work on disks in a narrow channel is entirely consistent with these ideas. In our earlier work [6,7] a length scale ξ associated with zigzag order has been determined from the decay with s of the correlation function y i y i+s ∼ (−1) s exp(−s/ξ) .…”
Section: Fig 1: (Color Online)supporting
confidence: 74%
“…Our system is sufficiently simple that we can quantitatively relate its dynamical features to structural features. The threedimensional problem is much richer and success along these lines is probably only just starting [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by Cubuk et al [20] on the flow of jammed and glassy systems under stress has shown that regions that are susceptible to rearrangement can be discovered by machine-learning methods that combine information derived from several features of the local structure, such as the radial distribution of particles and the bond angles. Since our narrow-channel system with NNN contacts is relatively simple, we are able to identify the collective motions of the disks that lead to the apparent ideal glass behaviors.…”
Section: Introductionmentioning
confidence: 99%